Focus on grammar intermediate level - Fuchs, Majorie; Bonner, Margaret (New York : Addison-Wesley Publishing, 1996)
The interactive multimedia program for learners of English
Guide to use: 1. Install the program by follow the instruction given. 2. Go to start - program to use the cd (do not take out the cd when running this course)
Keywords: English language -- Grammar -- Problems, exercises, etc